Revolusi Teknologi Komunikasi Dalam Dinamika Masyarakat Informasi: Mengulik Tiga Pendekatan Techno-Komunikasi - Mudjiyanto, Bambang; Launa, Launa; Lusianawati, Hayu (Universitas Bung Karno, 2024)
ABSTRACTIn media studies there are three approaches to understanding the development of informationtechnology (techno-communication), namely the dystopian, neo-futurist and techno-realistapproaches. These three approaches, until today, are at least considered to represent anacademic sketch in understanding the development of Communication technology. This studyis to see the dynamics and development of the information society, which is considered bysome to be a real threat to the existence of human values, authenticity in social life relations,and even the potential to damage political life and democracy. Through a qualitative researchapproach with a descriptive analysis method, this study tries to conduct a literature study toachieve a complete and objective understanding of the problematic issue. The results of thestudy show that the discourse of the communication technology revolution in the dynamics ofthe information society is still academically problematic, because each school of thought(dystopian, neo-futurist, and techno-realist) has philosophical reasons, academic arguments,and empirical evidence that show relevant and equally strong arguments for each of theirclaims. What needs to be considered is: how to correlate the information technologyrevolution with the readiness (literacy) of the community as users; and how to position thedevelopment of communication technology in line with human needs, as a support for humanlife, not the other way around, making humans more objects of technology.Keyword: technology revolution, techno-communication, network society, dystopian, neofuturist, techno-realist